2010
DOI: 10.1213/ane.0b013e3181e1e9ab
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Fentanyl to Local Anesthetics Affects the Quality and Duration of Cervical Plexus Block

Abstract: The addition of fentanyl to local anesthetics improved the quality and prolonged the duration of cervical plexus block in patients undergoing CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 16 publications
2
25
0
1
Order By: Relevance
“…Prolongation of postoperative analgesia was reported in other studies also. 25 In our study we observed a significant prolongation of duration of analgesia with addition of fentanyl to local anaesthetics. Murphy DB et al 4,9 in their systematic review on analgesic adjuncts for brachial plexus block pointed out that evidences for analgesic benefit with addition of opioids in brachial plexus block over systemic opioids are minimal.…”
Section: Discussionsupporting
confidence: 47%
“…Prolongation of postoperative analgesia was reported in other studies also. 25 In our study we observed a significant prolongation of duration of analgesia with addition of fentanyl to local anaesthetics. Murphy DB et al 4,9 in their systematic review on analgesic adjuncts for brachial plexus block pointed out that evidences for analgesic benefit with addition of opioids in brachial plexus block over systemic opioids are minimal.…”
Section: Discussionsupporting
confidence: 47%
“…To the best of our knowledge, the present study is the first to investigate the effects of fentanyl addition to the TAP block on postoperative analgesia. A 2.5 µg/ml fentanyl dose (total dose, 100 µg) was selected in the present study, since previous studies have demonstrated that this concentration of fentanyl was able to significantly improve the effectiveness of peripheral nerve blocks (9)(10)(11)14). Furthermore, this dose was selected due to concerns regarding potential dose-dependent adverse systemic effects associated with fentanyl.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, various opioids, including fentanyl and sufentanil, have been shown to exert LA-like effects (8). However, the effects of opioids on peripheral nerve blocks are controversial; previous studies have reported both positive and negative effects for opioids (9)(10)(11)(12)(13)(14)(15)(16)(17). To the best of our knowledge, the use of opioids as analgesic adjuncts to the TAP block for postoperative analgesia are yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…17 Prolongation of postoperative analgesia was reported in other studies also. 18 We also observed a significant prolongation of duration of analgesia with addition of fentanyl to local anaesthetics. Damien et al in their systematic review on analgesic adjuncts for brachial plexus block pointed out that evidences for analgesic benefit with addition of opioids in brachial plexus block over systemic opioids are minimal.…”
Section: Discussionmentioning
confidence: 59%